Social support in the structure of personal resources of internally displaced persons - Chuiko, Helen; Holotenko, A. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
The article reveals the results of an empirical study aimed at identifying the role and place of social support in the structure of the personal resources of internally displaced persons. Revealed correlations indicate the existence of trends, fixing the passivity and inertia of aid recipients, which could become the basis for the formation of consumer behavior and the emergence of manifested destructive personality.